Effectiveness of Learning Using IWU 's E-learning on Satisfaction and its Impact on Motivation Study International Women University Students during the Covid 19 Pandemic - A Ramadhina, Fifi; Narimawati, Umi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2022)
The COVID-19 pandemic has changed a new paradigm of learning in universities, including at the International Women's University. It’s fully realized that it’s not easy to change someone's habits, including the habit of learning methods that have been implemented, namely face-to-face. Almost 2 years of learning for IWU students have changed from face-to-face to elearning. The favorable condition is the phenomenon of age who use the internet more often, dominated by the age of 19-24 years, which is the second largest in Indonesia. Therefore, IWU’s e-learning-based learning is a substitute solution for face-to-face learning.Various problems arise and what is being questioned is the perceived decrease in student motivation as a result of the implementation of learning using e-learning. Lack of monitoring of student attendance in lectures, lack of control over the achievements of each student, as well as the presence of some students who want face-to-face learning to be implemented immediately. This study aims to determine the effectiveness of learning using e-learning on satisfaction and its implications for learning motivation in International Women University students. The descriptive method with a quantitative approach is used in this study with a total sample of 356 respondents from a total of 3234 students using the Slovin formula. Analysis using the SPSS 20 for windows software program was used in this study. Questionnaires were collected through the distribution of google forms. The results of this study indicate that the effectiveness of learning using IWU's elearning is an effective solution to create student satisfaction and has implications for student motivation at International Women's University